ДЕМОКРАТИЯЛЫҚ ҚӘДИРИЯТЛАРДЫҢ КӨРКЕМ ДӨРЕТИӮШИЛИКТЕГИ ТАЛҚЫСЫ (Т.Жумамуратов шығармалары мысалында) - Джумамуратова, М.Т. (SCIENCE and SOCIETY, 2020)
The article is devoted to the interpretation of democratic values in artistic creation on the example of the works of the Karakalpak poet Tleubergen Zhumamuratov. The poet's artistic thinking about a legal-democratic society, public administration and legal protection are explained. The main emphasis of the analyzes is aimed at spiritual and moral assessment in works, values such as spirituality, humanity and justice are brought to the fore.
Keywords: democratic values; artistic creation; thinking; public consciousness